Mitochondrial complex I abnormalities underlie neurodegeneration and cognitive decline in Alzheimer’s disease - Terada, Tatsuhiro; Therriault, Joseph; Kang, Min Su; Savard, Melissa; Pascoal, Tharick Ali; Lussier, Firoza; Tissot, Cecile; Wang, Yi‐Ting; Benedet, Andrea; Poltronetti, Nina Margherita; Ottoy, Julie; Arias, Jaime Frenandez; et al. (European journal of neurology, 2022)
Background and purpose Abnormal mitochondrial metabolism has been described in the Alzheimer's disease (AD) brain. However, the relationship between AD pathophysiology and key mitochondrial processes remains elusive. The purpose of this study was to investigate whether mitochondrial complex I dysfunction is associated with amyloid aggregation or glucose metabolism and brain atrophy in patients with mild AD using positron emission tomography (PET). Methods Amyloid‐ and tau‐positive symptomatic AD patients with clinical dementia rating 0.5 or 1 (N = 30; mean age ± standard deviation: 71.8 ± 7.6 years) underwent magnetic resonance imaging and PET scans with [18F]2‐tert‐butyl‐4‐chloro‐5–2H‐pyridazin‐3‐one (BCPP‐EF), [11C]Pittsburgh Compound‐B (PiB) and [18F]fluorodeoxyglucose (FDG) to assess brain atrophy, mitochondrial complex I dysfunction, amyloid deposition, and glucose metabolism, respectively. Local cortical associations among these biomarkers and gray matter volume were evaluated with voxel‐based regressions models. Results [18F]BCPP‐EF standardized uptake value ratio (SUVR) was positively correlated with [18F]FDG SUVR in the widespread brain area, while its associations with gray matter volume were restricted to the parahippocampal gyrus. Reductions in [18F]BCPP‐EF SUVR were associated with domain‐specific cognitive performance. We did not observe regional associations between mitochondrial dysfunction and amyloid burden. Conclusions In symptomatic cases, although mitochondrial complex I reduction is linked to a wide range of downstream neurodegenerative processes such as hypometabolism, atrophy, and cognitive decline, a link to amyloid was not observable. The data presented here support [18F]BCPP‐EF as an excellent imaging tool to investigate mitochondrial dysfunction in AD. The purpose of this study was to investigate whether mitochondrial complex I dysfunction is associated with amyloid aggregation, or glucose metabolism and brain atrophy in patients with amyloid‐ and tau‐positive mild Alzheimer's disease using positron emission tomography. The study demonstrated that mitochondrial complex I dysfunction ([18F]BCPP‐EF) correlated significantly with glucose hypometabolism ([18F]FDG), gray matter volume reduction (magnetic resonance imaging), and domain‐specific cognitive performance. The correlation with amyloid ([11C]PiB) was not observable. The study indicated that mitochondrial dysfunction mirrors neurodegeneration and cognitive decline, but not amyloid pathology.